Increased Corticomuscular Coherence in Idiopathic REM Sleep Behavior Disorder - Jung, Ki-Young; Cho, Jae-Hyun; Ko, Deokwon; Seok, Hung Youl; Yoon, Ho-Kyoung; Lee, Heon-Jeong; Kim, Leen; Im, Chang-Hwan (Frontiers in Neurology, 2012)
The authors hypothesized that if locomotor drive increases along with rapid eye movement (REM) sleep without atonia in idiopathic REM sleep behavior disorder (RBD), then RBD patients would have greater corticomuscular coherence (CMC) values during REM sleep than at other sleep stages and than in healthy control subjects during REM sleep. To explore this hypothesis, we analyzed beta frequency range CMC between sensorimotor cortex EEG and chin/limb muscle EMG in idiopathic RBD patients. Eleven drug naive idiopathic RBD patients and 11 age-matched healthy control subjects were included in the present study. All participants completed subjective sleep questionnaires and underwent polysomnography for one night. The CMC value between EEGs recorded at central electrodes and EMGs acquired at leg and chin muscles were computed and compared by repeated measures analysis of variance (ANOVA). Sleep stages and muscle (i.e., chin vs. leg) served as within-subject factors, and group served as the between-subject factor. Repeated measures ANOVA revealed no significant main effect of group (F1,20=0.571, p=0.458) or muscle (F1,20=1.283, p=0.271). However, sleep stage was found to have a significant main effect (F2.067,41.332=20.912, p<0.001). The interaction between group and sleep stage was significant (F2.067,41.332=3.438, p=0.040). RBD patients had a significantly higher CMC value than controls during REM sleep (0.047±0.00 vs. 0.052±0.00, respectively, p=0.007). This study reveals increased CMC during REM sleep in patients with RBD, which indicates increased cortical locomotor drive. Furthermore, this study supports the hypothesis that sufficient locomotor drive plays a role in the pathophysiology of RBD in addition to REM sleep without atonia.